Alcohol (70%) versus alcoholic chlorhexidine solution (0.5%) in skin antisepsis for neuraxial blocks: a randomized clinical trial - TOSTES,LUIZ CARLOS SOUZA (2021)
ABSTRACT Objective: to compare the use of 0.5% alcoholic chlorhexidine and 70% alcohol in skin antisepsis for neuraxial blocks. Method: this is a non-inferiority randomized clinical trial, with two parallel arms. Seventy patients who were candidates for neuraxial block were randomly allocated to group A (n = 35), in whom antisepsis was performed with 0.5% alcoholic chlorhexidine, or to group B (n = 35), in whom we used 70% hydrated ethyl alcohol. Swabs were harvested for culture at three times: before antisepsis, two minutes after application of the antiseptic, and immediately after puncture. The samples were sown in three culture media and the number of colony forming units (CFU) per cm² was counted. Results: there was no difference between the groups regarding age, sex, body mass index, time to perform the block or type of block. There were no differences between groups in the CFU/cm² counts before antisepsis. There was less bacterial growth in group B two minutes after application of the antiseptic (p = 0.048), but there was no difference between the groups regarding the number of CFU/cm² at the end of the puncture. Conclusion: 70% alcohol was more effective in reducing the number of CFU/cm² after two minutes, and there was no difference between the two groups regarding skin colonization at the end of the procedure. These results suggest that 70% alcohol may be an option for skin antisepsis before neuraxial blocks. Trial registration: ClinicalTrials.gov, NCT02833376.